Neonatal outcome in pregnancies that presented premature rupture of membranes - Silveira, Marcela Lima (2014)
This study aimed to describe the neonatal outcomes of infants whose mothers had premature rupture of membranes during pregnancy. This is a retrospective, descriptive, quantitative study performed in a public maternity in Fortaleza-CE, Brazil, with 166 neonates of mothers with premature rupture of membranes, in 2010. Data were collected through research in medical records using a pre-structured form. There was a predominance of newborns at term with good birth weight and adequate vitality. Statistical analysis showed significant association between prematurity and prolonged latency and neonatal variables: need for respiratory support, neonatal infection and antibiotic use. It was concluded that gestational age has fundamental importance to conduct clinical management and prognostic evaluation of perinatal outcomes, as the main health problems related to premature rupture of membranes result from prematurity.